Mapping the Groundwater Potentiality of West Qena Area, Egypt, Using Integrated Remote Sensing and Hydro-Geophysical Techniques - Ahmed Gaber; Adel Kamel Mohamed; Ahmed ElGalladi; Mohamed Abdelkareem; Ahmed M. Beshr; Magaly Koch (Remote Sensing, 2020)
The integrated use of remote sensing imagery and hydro-geophysical field surveys is a well-established approach to map the hydrogeological framework, and thus explore and evaluate the groundwater potentiality of desert lands, where groundwater is considered as the main source of freshwater. This study uses such integrated approach to map the groundwater potentiality of the desert alluvial floodplain of the Nile Valley west of Qena, Egypt, as alternative water source to the River Nile. Typically ground gradient, faults and their stress field, lateral variation of rock permeability, drainage patterns, watersheds, rainfall, lithology, and soil types are the main factors believed to affect the groundwater recharge and storage from the infiltration of present-time and paleo-runoff. Following this generally accepted approach, different remote sensing data sets (SRTM DEM, Landsat-8, ALOS/PALSAR-1, Sentinel-1, and TRMM) as well as auxiliary maps (geological and soil maps) were used to identify and map these factors and prepare thematic maps portraying the different influences they exert on the groundwater recharge. These thematic maps were overlaid and integrated using weights in a GIS framework to generate the groundwater potentiality map which categorizes the different recharge capabilities into five zones. Moreover, the aeromagnetic data were processed to map the deep-seated structures and estimate the depth to basement rocks that may control the groundwater occurrence. In addition, the vertical electrical sounding (VES) measurements were applied and calibrated with the available borehole data to delineate the subsurface geological and hydrogeological setting as well as the groundwater aquifers. Different geoelectric cross-sections and hydro-geophysical maps were constructed using the borehole information and VES interpretation results to show the lateral extension of the different lithological units, groundwater-bearing zones, water table, and the saturated thickness of the aquifer. The GIS model and geophysical results show that the southwest part of Nag’a Hammadi-El-Ghoneimia stretch has very high recharge and storage potentiality and is characterized by the presence of two groundwater-bearing zones. The shallow groundwater aquifer is located at a depth of 30 m with a saturation thickness of more than 43 m. However, there are NW–SE faults crossing the study area and most likely serve as recharge conduits by connecting the shallow aquifer with the deeper ones. Such aquifers connection has been confirmed by investigating the chemical and isotopic composition of their groundwater.